Luc 16,1-8.9-13 et l'intratextualité lucanienne - Aletti, Jean-Noël (Biblica, 2024)
The aim of this essay is essentially methodological, i.e., to show that a close analysis of the parable in Luke 16,1-8 is necessary to arrive at a correct interpretation. To be complete and reliable, narrative analysis must also include the intratextuality of the macro-narrative, but this examination of the proximate and remote context must not precede narrative analysis, only follow it. To be coherent, the narrative analysis of Lucan parables must avoid immediately resorting to allegoresis but must first check whether the parable analyzed has the coherence and characteristics of narratives.